Resilient Cities and Land Take Effective Management Through Sustainable Urban Planning Tools - Debora Anelli; Pierluigi Morano; Marco Locurcio; Francesco Tajani (Land)
In the contemporary context of cities’ increasing exposure to climate risks and the fragility of urban infrastructure and soil productivity, the concept of urban resilience is central to sustainable planning processes [...]